Values and employees' voluntary pro-environmental behaviour in small, medium and micro enterprises in Polokwane Municipality - Motebejane, Kabelo Nankie (My University, 2022)
The primary objective of the study was to examine the effect of values (biospheric values, altruistic values, egoistic values and openness to change values) on voluntary pro-environmental behaviour of employees of SMMEs.In addition, the study investigated the moderating effect of demographic variables (gender, age and level of education) in the relationship between values and pro-environmental behaviour. The quantitative approach was utilised and the cross-sectional survey method was used to collect data from the respondents that were conveniently sampled. The Cronbach’s alpha was used to measure reliability and the Partial Least Square Structural Equation Modelling (PLS SEM) was utilised to analyse data. The findings of the study indicated that biospheric values has a negative relationship with employees’ voluntary proenvironmental behaviour. Three values (altruistic, egoistic and openness to change values) have significant positive relationships with voluntary pro-environmental behaviour of employees. The moderating effects of gender, age and level of education are insignificant. Recommendations on how to use values to improve the voluntary pro-environmental behaviour of employees of SMMEs are outlined.
Thesis (M.Com. (Business Management)) -- University of Limpopo, 2022
Keywords: Pro-environmental behaviour; Biospheric values; Altruistic values; Egoistic values; Openness to change values; Value belief norm theory; Employees’ voluntary pro-environmental behaviour; Environmental protection; Employees; Values; Small Businesses